Performance improvement of developed program by using multi-thread technique - Jabal, Surasak; Ung-arunyawee, Rujchai (Engineering and Applied Science Research, 2015)
This research presented how to use a multi-thread programming technique to improve the performance of aprogram written by Windows Presentation Foundation (WPF). The Computer Assisted Instruction (CAI) software, named GAME24, was selected to use as a case study. This study composed of two main parts. The f irst part was about design and modif ication of the program structure upon the Object Oriented Programing (OOP) approach. The second part was about coding the program using the multi-thread technique which the number of threads were based on the calculated Catalan number. The result showed that the multi-thread programming technique increased the performance of the program 44%-88% compared to the single-thread technique. In addition, it has been found that the number of cores in the CPU also increase the performance of multithreaded program proportionally.